Feminist Collections, v.1, no.1 (February 1980) - (:unkn) unknown (Women's Studies Librarian, 1980)
First issue of the periodical FEMINIST COLLECTIONS: A QUARTERLY OF WOMEN'S STUDIES RESOURCES. Original subtitle: WOMEN'S STUDIES LIBRARY RESOURCES IN WISCONSIN. 6p. No table of contents.
Intent of the publication: "...reflects our desire to establish a network among persons with an interest in library-related issues in Women's Studies. Establishing communication networks is an important effort for any discipline, and especially so for an interdisciplinary area such as Women's Studies. The newsletter will offer information about feminist library presses, periodical reviews, book reviews, media reviews, descriptions of library activities in Women's Studies at the campuses in the UW System, announcements of conferences and workshops, discussion of issues such as intellectual freedom in developing Women's Studies library collections, problems in access to materials, and descriptions of microform collections owned by libraries in the state." Describes a Special Collection on Wisconsin Women Artists; a Women's Studies Union List(WSUL)-- a card catalog of recent acquisitions on subjects relating to women from University of Wisconsin System libraries; and includes a book review of Personal Politics: The Roots of Women's Liberation in the Civil Rights Movement pdd the New Left, by Sara Evans.
Keywords: Women's Studies; Gender; Feminism; Library Resources; Reviews